Proton pump inhibitors are associated with hypersensitivity reactions to drugs in hospitalized patients: a nested case‐control in a retrospective cohort study. Issue 3 (17th February 2013) - Ramírez, E.; Cabañas, R.; Laserna, L. S.; Fiandor, A.; Tong, H.; Prior, N.; Calderón, O.; Medrano, N.; Bobolea, I.; Frías, J.; Quirce, S.
Summary Background Previous research has shown that gastric acid suppression by antacid drugs can promote allergic reactions to acid‐labile food proteins. No data are available about whether antacid drugs can promote drug hypersensitivity reactions. The most potent and longer lasting inhibition of gastric secretion is provided by proton pump inhibitors (PPIs). We hypothesized that gastric acid suppression by proton pump inhibitors could be causative of drug hypersensitivity reactions during hospitalization. Objective To estimate the risk of developing drug hypersensitivity reactions during the hospitalization of patients treated with proton pump inhibitors, and other associated factors. Methods A nested case‐control in a retrospective cohort study of hospitalized patients from September 2008 to December 2010 (70 771 admissions) was conducted using the registry of cases of interconsultations to the Allergy Department (161 confirmed cases of drug hypersensitivity reactions). A total of 318 controls were matched by first drug suspected in the hypersensitivity reaction, time of admission, age, gender and hospitalization wards. Results The relative risk of drug hypersensitivity reaction occurrence during hospitalization of patients treated with PPIs compared with those not treated in the period of study was significant (RR: 3.97; 95% CI: 1.97–8.29). After controlling for confounders in the nested case‐control cohort, the use of PPIs persists as a predisposing factor (OR: 4.35; 95% CI: 2–9.45). Personal history of drug allergy and a long hospitalization time were other predisposing factors of drug hypersensitivity reactions (DHRs). The hazard that a DHR has occurred during PPI treatment was 3.7% per day. The hazard for immediate or accelerated reactions was 1.706 (P = 0.003) times that of delayed reactions. Conclusion and Clinical Relevance In hospitalized patients, the use of proton pump inhibitors was associated with a significant increase risk of drug hypersensitivity reactions along with a personal history of drug allergies and long hospitalization time.